Nationalism vs. Christian Faith: A Bible Review - Rajiman Andrianus Sirait; Timotius Sukarna (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
This article explores the relationship between nationalism and Christian faith from a biblical perspective. Nationalism is often defined as loyalty to nation and state, while Christian faith centres on loyalty to God and His kingdom. In the Indonesian context, churches participated in the nationalism movement from the colonialism era until independence. Based on theological studies, the Bible provides insight that believers' primary loyalty should be to God, although they are also expected to be good citizens. This article uses a literature study method with a qualitative approach to analyse relevant biblical texts as well as related theological literature. The concept of nation in the Bible is examined from the perspective of the Old Testament, which focuses on the ethnic identity of the nation of Israel, to the New Testament, which expands the nation's identity into an inclusive community of faith. The article also highlights the ethical implications of nationalism for Christians, who should reflect the values of justice, love and sacrifice, and avoid exclusionary and xenophobic attitudes.